Tumor Necrosis Factor-α Mediates Orthopedic Implant Osteolysis - Merkel, Kurt D. (American Society for Investigative Pathology, 1999)
Osteolysis complicating arthroplasty reflects progressive generation of implant-derived wear particles, which prompt an inflammatory reaction attended by recruitment of osteoclasts to the prosthesis-bone interface. To identify a soluble mediator of peri-prosthetic osteolysis we first showed that implant particles induce c-src in murine bone marrow macrophages (BMMs), a protein specifically expressed when these cells commit to the osteoclast phenotype. The fact that tumor necrosis factor-α (TNF) is a potent osteoclastogenic agent while at the same time is the only soluble moiety known to be c-src inductive suggests that this cytokine may mediate implant particle-induced osteoclastogenesis. Consistent with this hypothesis, prosthesis-derived wear particles, recovered at revision arthroplasty, dose-dependently prompt TNF secretion by BMMs. Similarly, particulate polymemthylmethacrylate, the major component of orthopedic implant cement, induces BMM expression of TNF mRNA and protein in a time- and dose-dependent manner. Furthermore, failure of BMMs derived from mice deleted of both the p55 and p75 TNF receptors to express c-src in response to polymemthylmethacrylate indicates TNF is an essential mediator of particle induction of this osteoclast specific protein. To test the hypothesis that TNF mediates implant osteolysis, we established an in vivo murine model of this condition that histologically mirrors that of man. Verifying that TNF is essential to development of particle osteolysis, mice failing to express both the p55 and p75 TNF receptors are protected from the profound bone resorption attending polymemthylmethacrylate particle implantation on calvariae of wild-type animals. Finally, the protective effect of deletion of both TNF receptors is recapitulated in mice lacking only the p55 receptor. Thus, targeting TNF and/or its p55 receptor may arrest wear particle osteolysis.